IMPLEMENTASI TEMPAT SAMPAH PINTAR BERBASIS IoT (INTERNET of THINGS) UNTUK MONITORING LIMBAH MEDIS (STUDI KASUS LEMBAGA PELATIHAN PUSDIKMIN POLRI JAWA BARAT) - Solihin . (Scientia Regendi, 2022)
Waste management is currently a fairly important topic of concern, the need for waste management information that can control the environmental situation to be maintained from air collusion is quite important. For an officer working in a waste area, waste-related information will be very useful to know where they should prioritize waste-handling activities. During the current Covid-19 pandemic, the capacity of waste contents is not just ordinary waste, but mixed with medical waste, such as disposable masks, tissues, and disposable gloves, if medical waste is allowed to accumulate for too long it will be badly impacted in the surrounding environment, the trash can needs to be monitored and controlled to ensure a healthy and clean environment. This study presents the design and implementation of an Internet of things (IoT)-based Arduino microcontroller that works with MQ-135 sensors of chemical sensor types that are sensitive to NH3 compounds, NOx, alcohol, benzols, smoke (CO), and CO2. As well as ultrasonic sensors that can detect waste volume levels and periodically display information on LCD screens and with Wifi modules web server systems display status-related information, volume, hazard level, and safe from the trash can in real-time. This process helps monitor and control medical waste in the trash can. Many tests were carried out to evaluate the working capabilities of the device in real-time. The measured distance from the bin is transmitted to the website, this web page performs analytics and visualization diagrams that show the status and level of medical waste, time, and location in real-time. The results of the MQ-135 Gas Sensor testing of the concentration of substances detected on a ppm scale (part per million), the normal limit of medical waste is at the level of 314 ppm with a safe time of 5 -20 minutes, for bad or hazard levels at the level of >523 ppm time of >25 minutes is a situation that must be carried out waste removal measures.